Winners and losers in industrial policy 2.0 - Mohamed Ali Marouani; Michelle Marshalian (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Large-scale business subsidies tied to national industrial development promotion programmes are notoriously difficult to study and are often inseparable from the political economy of large government programmes. We use the Tunisian national firm registry panel database, data on treated firms, and a perceptions survey administered by the National Research Institute to measure the impact of Tunisia's Industrial Upgrading Program. Using inverse propensity score re-weighted differences-in-differences regressions, we find that small treated firms hire more and higher-skilled labour. In small firms, wages increase 10-17 per cent, with growth in employment and net job creation. However, in larger firms the programme does not support labour and wages fall, suggesting that there are no benefits to labour when funds go to large firms.
Keywords: H2; O1; L2; O2; 330; Entwicklungsländer; Developing countries; Steuerpolitik; Tax policy